2016
DOI: 10.1037/cap0000073
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of children with refugee statuses: A research review.

Abstract: Over the past several decades, an increasing number of refugee children and families have involuntarily migrated to countries around the world to seek safety and refuge. As the refugee population increases, it is becoming more important to understand factors that promote and foster resilience among refugee youth. The present review examines the past 20 years of resilience research with refugee children to identify individual, family, school, community, and societal factors fostering resilience. This review hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 55 publications
(157 reference statements)
8
111
0
5
Order By: Relevance
“…The importance of families-not simply parents-was made apparent in this research, and our results echo the work of Castro and Murray (2010), Ni, Li, and Zhao (2014), and Pieloch, McCullough and Marks (2016) in pointing to the importance of families in explaining the stress and efforts to cope that immigrant students experience. Frujas Amthor and Roxas (2016) have reviewed significant research suggesting that separation from extended families can be a major source of stress and trauma for immigrating students.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The importance of families-not simply parents-was made apparent in this research, and our results echo the work of Castro and Murray (2010), Ni, Li, and Zhao (2014), and Pieloch, McCullough and Marks (2016) in pointing to the importance of families in explaining the stress and efforts to cope that immigrant students experience. Frujas Amthor and Roxas (2016) have reviewed significant research suggesting that separation from extended families can be a major source of stress and trauma for immigrating students.…”
Section: Resultssupporting
confidence: 78%
“…In their literature review, Pieloch, McCullough & Marks (2016) organized factors into individual, family, school, community and societal categories, but we found that our organization might be more relevant to work with immigrant students in educational settings.…”
Section: The Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of social support is vital for the resilience of the immigrant group (Pieloch, McCullough, & Marks, 2016). However, immigrants often face various prejudices such as ethnocentrisms, racism and economic discrimination (Ellis, MacDonald, Klunk-Gillis, Lincoln, Strunin, & Cabral, 2010;Yakushko & Morgan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Auk menntunar, og í samraemi við lög og námskrár íslenskra skóla, þá gefur skólinn börnum taekifaeri til að umgangast jafningja og eignast nýja vini (McCarthy og Marks, 2010; Perez-y-Perez, Marin, Joseph og Evans, 2011; Tonheim o.fl., 2015). Samskipti við skólafélaga geta haft góð áhrif á vellíðan barnanna ef vel tekst til en framkoma skólafélaga við þau skiptir þau miklu máli (Correa-Velez, Gifford og Barnett, 2010; Fazel, 2015; Kia-Keating og Ellis, 2007;Pacione, Measham og Rousseau, 2013;Pastoor, 2015;Pieloch, McCullough og Marks, 2016;Spicer, 2008). Einnig getur þátttaka í tómstundastarfi veitt þessum hópi barna útrás og stuðlað að baettri sálfélagslegri vellíðan þeirra (Beirens, Hughes, Hek og Spicer, 2007;Kalksma-Van Lith, 2007;Tonheim o.fl., 2015).…”
Section: Fraeðilegur Bakgrunnurunclassified